2013
DOI: 10.1121/1.4803520
|View full text |Cite
|
Sign up to set email alerts
|

Guided wave mode selection for health monitoring of sub-surface hidden defects on fuel weep holes

Abstract: The in situ health monitoring of defects on the blind side of open holes using ultrasonic plate waves is a challenging problem. Scattering phenomena in this hard-to-inspect region can be used indicate the presence of the defect. This is especially advantageous if these phenomena give rise to the scattering of a wave mode that is unique to the interaction between the incident wave mode and defect. When the defect in question is located within an inaccessible structure, an understanding of how the incident ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…On further investigation Doherty and Chiu [9] found a clear generation of an SH0 mode at the tip of the notch using a scatter plot. As shown in Fig.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…On further investigation Doherty and Chiu [9] found a clear generation of an SH0 mode at the tip of the notch using a scatter plot. As shown in Fig.…”
Section: Introductionmentioning
confidence: 95%
“…On progress this SH0 wave travels as an edge guided wave. This wave scatters into the medium and finally surfaces as a Rayleigh-type wave [9]. This paper will present a computational study aimed at better understanding the interaction of edge guided waves with crack tips, with a view to developing a quantitative inspection methodology suitable for crack sizing in hard-to-inspect locations.…”
Section: Introductionmentioning
confidence: 99%
“…The drawback with this traditional application of ultrasonic waves for damage detection is that it is often restricted to detecting damages in the immediate vicinity of the acoustic source and hence requires time-consuming scanning for wide-area inspection [5]. The use of Lamb waves is a widely studied alternative, which has the potential to scan entire plates and detect damage that is not in direct line of sight of the source [6]. Studies have shown great promise in the diagnostic ability of Lamb waves in detecting several types of defect: cracks, corrosion and delamination damage [7].…”
mentioning
confidence: 99%